CP-180 Reasons for switching from integrase inhibitors in a real cohort of hiv patients during a 3 year study. (25th February 2017) - Antonio-Cuscó, M De; Luque, S; González-Colominas, E; Ferrández, O; Monge-Escartin, I; Knobel, H; Salas, E
Abstract : Background: Integrase inhibitors (INSTIs) are recommended as firstline antiretroviral treatment (ART) in HIV patients. However, several factors such as toxicity, virological failure or a low adherence can lead to a switch of ART. Purpose: To assess the frequency and compare the reasons for switching among the INSTIs in a HIV unit in a tertiary hospital. Material and methods: A retrospective study including all patients who switched from INSTIs to other ART (January 2014–September 2016) in our cohort of 1750 HIV infected patients was conducted. Switches involving ART other than INSTIs were not included. Data collected: demographics, hepatitis C virus coinfection, previous and new ART. Reasons for switching were classified as: adverse events (neuropsychiatric toxicity, dermatologic, gastrointestinal and others), schedule optimisation (convenience, simplification or food restrictions), drug–drug interactions, pregnancy and low level viraemia (LV). Results: 733 patients were treated with INSTIs during this period: 223 (30.4%) raltegravir, 159 (21.7%) elvitegravir and 351 (47.9%) dolutegravir. The INSTI was switched in 133 patients (7.2% of total patients): 101 (75.9%) men, age 47.0±13.2 years, HCV 39 (29.3%). New ART treatment included INSTIs in 97 (72.9%) (6% raltegravir; 24.8%elvitegravir; 42.1% dolutegravir); non-nucleoside reverse transcriptase inhibitors in 11 (8.3%); protease inhibitors in 20 (15.0%); and others ART in 5 (3.8%) patients. Conclusion: In more than 50% of patients, the INSTIs were switched in order to optimise the ART schedule. Raltegravir was the INSTI more frequently switched, because of schedule optimisation and presence of LV (due to poor adherence in almost all patients). Drug interactions leading to an INSTI switch were exceptional and were only seen with elvitegravir, probably related to its coformulation with cobicistat. The most common reason for stopping dolutegravir was adverse events, mostly gastrointestinal, while none of the patients experienced LV. No conflict of interest